2000
DOI: 10.1007/bf02236557
|View full text |Cite
|
Sign up to set email alerts
|

Artificial anal sphincter

Abstract: Artificial anal sphincter provided prolonged and reasonably good functional results in severe incontinence, reproducing an efficient sphincteric mechanism and allowing satisfactory anal occlusion and rectal emptying in approximately 75 percent of cases in this study. The definitive explantation rate was kept low by careful patient selection and appropriate surgical and perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Seventeen papers (Lehur et al, 1996;2000;Wong et al, 1996;Vaizey et al, 1998;Christiansen et al, 1999;Dodi et al, 2000;Malouf et al, 2000;O'Brien and Skinner, 2000;Altomare et al, 2001;Devesa et al, 2002;Ortiz et al, 2002;Parker et al, 2003;Casal et al, 2004;Ruiz Carmona et al, 2009;Chittawatanarat et al, 2010) reported the infection rate, which varied between 4% (Lehur et al, 2000) and 50% (Chittawatanarat et al, 2010). In three papers of Lehur et al (1996;2000), the frequencies of infection were 15%, 8%, and 4%, respectively.…”
Section: Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen papers (Lehur et al, 1996;2000;Wong et al, 1996;Vaizey et al, 1998;Christiansen et al, 1999;Dodi et al, 2000;Malouf et al, 2000;O'Brien and Skinner, 2000;Altomare et al, 2001;Devesa et al, 2002;Ortiz et al, 2002;Parker et al, 2003;Casal et al, 2004;Ruiz Carmona et al, 2009;Chittawatanarat et al, 2010) reported the infection rate, which varied between 4% (Lehur et al, 2000) and 50% (Chittawatanarat et al, 2010). In three papers of Lehur et al (1996;2000), the frequencies of infection were 15%, 8%, and 4%, respectively.…”
Section: Infectionmentioning
confidence: 99%
“…Four scoring systems were adopted: Williams Scale (WS), AMS Fecal Incontinence Score (AMSFIS), Cleveland Continence Score (CCS), and Wexner Continence Grading Score (WCGS) (Jorge and Wexner, 1993;Vaizey et al, 1999;Mundy et al, 2004), as shown in Table 1. Lehur et al (2000; used AMSFIS. The mean score decreased significantly from 106 (standard deviation (SD), 13) and 105 (SD,14) in the preoperative stage, to 25 (SD, 25) and 23 (SD,22) at the end of the follow-up period, respectively.…”
Section: Fecal Incontinence Scorementioning
confidence: 99%
See 1 more Smart Citation